2022
DOI: 10.1186/s12872-022-02546-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the right atrial phasic functions in patients with anterior ST-elevation myocardial infarction: a 2D speckle-tracking echocardiography study

Abstract: Background Evidence suggests that changes in left ventricular systolic and diastolic functions may affect right atrial (RA) phasic functions. We aimed to evaluate RA phasic functions in the presence of anterior ST-elevation myocardial infarction (ASTEMI) as an acute event and to compare the findings with those in a control group. Methods We recruited 92 consecutive ASTEMI patients without accompanying significant stenosis in the proximal and middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…[15] Right atrial volume and function have been identified as important prognostic indicators for a variety of cardiovascular diseases [16,17] and as independent predictors of outcomes in many older patients susceptible to heart disease. [18,19] The right atrium has long been a neglected chamber. However, it is the hub through which blood from the entire body flows into the heart, and its chronotropic function plays 3 important roles throughout the cardiac cycle [20,21] : Storage function: the tricuspid valve closes during the right ventricular is an important cardiac chamber that regulates ventricular filling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Right atrial volume and function have been identified as important prognostic indicators for a variety of cardiovascular diseases [16,17] and as independent predictors of outcomes in many older patients susceptible to heart disease. [18,19] The right atrium has long been a neglected chamber. However, it is the hub through which blood from the entire body flows into the heart, and its chronotropic function plays 3 important roles throughout the cardiac cycle [20,21] : Storage function: the tricuspid valve closes during the right ventricular is an important cardiac chamber that regulates ventricular filling.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Right atrial volume and function have been identified as important prognostic indicators for a variety of cardiovascular diseases [ 16 , 17 ] and as independent predictors of outcomes in many older patients susceptible to heart disease. [ 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Eisvand et al also found decreased right atrial function in patients with acute anterior myocardial infarction. In this collective RA contraction function was predictive of all-cause mortality or reinfarction during the follow-up period [ 25 ]. In a collective of 1235 patients with acute myocardial infarction (NSTEMI/STEMI) who underwent cardiac magnetic resonance imaging after successful PCI Schuster et al found that the RA reservoir and the RA conduit function was impaired and predictive for onset of heart failure and MACE [ 12 ].…”
Section: Discussionmentioning
confidence: 99%